Pengaruh Lokasi, Harga, dan Word of Mouth Terhadap Keputusan Pembelian pada Rumah Makan Mie Mustanir Cabang M. Yamin Kota Samarinda - Qothifah Risma Febriyanti; Tuti Wediawati Noor (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to determine the effect of location, price, and word of mouth on purchasing decisions partially and simultaneously. This study uses a type of quantitative research through an associative approach with a Likert scale. The sampling technique used in this study was accidental sampling technique with a sample of 105 respondents from consumers of Mustanir Noodle Restaurant, M. Yamin Branch. Hypothesis testing in this study using statistical software SPSS version 26. The results showed that partially the price and word of mouth variables had a significant effect on purchasing decisions, but the location variable had no significant effect partially on purchasing decisions. Simultaneously, the three variables have a significant effect on purchasing decisions at the Mustanir Noodle Restaurant, M. Yamin Branch.